Association between paediatric eye injuries, later aca-demic success and social performance - Nina Jovanović; Corinne Peek-Asa; Zhang Ling; Joe E Cavanaugh; Adel Smajlović; Srdjan Nikolovski; Emir Begagić; Igor Knezović (Medicinski glasnik, 2024)
Aim: To investigate an association between eye injury and later academic and social performance. Methods: A retrospective longitudinal study of taking measurements multiple times was conducted including all severe eye injuries admitted during 2011-2017 at the main regional clinic to investigate changes in academic success and social inclusion before and after an injury. Parents/caregivers were surveyed asking questions on academic performance, and community/social involvement. In 2023 data on employment status were obtained. Kappa (ĸ) and non-parametric Wilcox-on signed-rank test for multiple comparisons were used. For association of employment status and post-injury visual acuity Fisher score was tested. Results: The total sample for assessing social inclusion and academic success was 36 and 25 children, respectively. In the following academic year ĸ agreements decreased from 0.88 (p<0.001) comparing pre-injury with a one-year post to 0.5106 (p<.0001) in the second year and 0.4750 (p=0.003) in the third, suggesting a deteriorating trend. A comparison of academic success before injury to two and three years after injury showed the trend significantly worsening with time (p=0.005, and 0.003, respectively). No association between an eye injury and social inclusion, as well as between employment and final visual acuity was noticed. Conclusion: Our findings suggest no association between social inclusion, employment, and eye trauma, while in later years academic success may be more impacted by the eye injury. Due to eye injury unpredictability in childhood age, both an informed and supportive climate environment at home and school is essential to minimize deleterious responses to eye trauma.
Keywords: childhood trauma; ocular; academic achievement; social engagement